Original paperFunctioning and quality of life of patients with leg ulcers treated at dermatology wards - Bączyk, Grażyna; Talarska, Dorota; Zawirska, Agnieszka; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction: Crural ulcers occur in 17-20% of adults and are directly related to age – they rarely occur before the age of 60. With duration exceeding 9 months in over 50% of cases and a high relapse rate (more than 2 in 3 cases) they pose a major therapeutic and social problem. The cause of this disease is not only venous insufficiency, but also disorders of arteries, diabetes or even rheumatoid arthritis. All these elements make the therapy more complicated, which pushes up its costs. Chronic crural ulcers are often a cause of psychological discomfort, which may lead to depression and further exacerbate social isolation of patients suffering from this disease. Aim: The aim of this study is to demonstrate the association between quality of life and severity of the disease as well as patient self-care, mobility and social activity. The aforementioned aspects may be modified by properly planned patient care; hence the importance of validation of the influence of different factors on patients’ quality of life. To assess the functioning of living and quality of life of patients with leg ulcers. Material and methods: The study group consisted of patients diagnosed with chronic leg ulcer, according to the CEAP (Clinical, Etiologic, Anatomic, Pathophysiologic) classification adopted by the American Venous and International Society of Vascular Surgery in 1994. The research was conducted in the Department of Dermatology of Poznan Regional Hospital (in- and outpatient clinics). The examined group consisted of 85 patients suffering from leg ulcers or varicose veins. The group consisted of 85 patients (51% women). The average age was 63.97 ±12.76. Patients were given a questionnaire with questions divided into two sections. The demographic section contained questions regarding age, gender, education, place of living, marital status, offspring, and cohabitants. The second part included clinical data concerning patient’s history, symptoms and diagnostics. Clinical information was used to assess the degree of venous insufficiency severity according to different classifications: clinical, aetiological, anatomical, and pathophysiological. Patients with crural ulcers also completed the CIVIQ questionnaire. Conclusions: Chronic Venous Insufficiency Questionnaire is a questionnaire for measuring quality of life. It consists of 20 questions in 4 areas: physical, psychological, social and pain. Research on the evaluation of the functioning and quality of life of patients with leg ulcers in patients treated at dermatology wards showed very poor functioning and poor quality of life of patients.